High-strength and high-plasticity thermoelectric composite material and preparation method and application thereof

By introducing nano-TiB2 into thermoelectric materials and optimizing sintering process, the problem of insufficient strength and stability of existing thermoelectric materials at room temperature is solved, and a thermoelectric composite material with high strength, high plasticity and high thermoelectric properties is realized, with a wide range of thermoelectric Device application potential.

CN119241241AActive Publication Date: 2025-01-03DALIAN UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411368119.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Existing thermoelectric materials have low strength, brittleness and poor processing properties at room temperature, and have poor structural stability, making it difficult to meet the needs of high thermoelectric performance and high strength.

Method used

Using Mg3.2Sb1.5Bi0.49Te0.01-xTiB2 thermoelectric composite material, nano-TiB2 is introduced through ball milling and sintering processes in an inert atmosphere to improve Zebeck coefficient and thermal conductivity, and by regulating the content and sintering parameters of TiB2, Optimize the mechanical properties of the material.

Benefits of technology

The thermoelectric composite material with high strength, high plasticity and high thermoelectric properties has excellent mechanical properties and processability. The room temperature thermoelectric superiority is 0.64, the mean thermoelectric superiority is 1.24 in the range of 323 to 773K, and the Vickers hardness and The compressive strength has been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241241A_ABST
    Figure CN119241241A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermoelectric materials, and particularly relates to a high-strength and high-plasticity thermoelectric composite material and a preparation method and application thereof. The nano TiB2 is introduced, the nano TiB2 and a matrix can form an energy barrier, and the Zebeck coefficient is improved under the condition that the conductivity is not obviously reduced; meanwhile, the heat conductivity is optimized and adjusted together with nanopores generated by sintering, and finally, the power factor and the heat conductivity of the material are synergistically optimized; and the composite nano TiB2 also enhances the mechanical properties of the material. The thermoelectric composite material provided by the invention has the advantages of high plasticity, high compressive strength, high hardness, high thermoelectric property, excellent mechanical property, good machinability, non-toxic elements and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermoelectric materials, and in particular relates to a high-strength and high-plasticity thermoelectric composite material and a preparation method and application thereof. Background Art

[0002] Thermoelectric materials have attracted extensive attention due to their ability to convert thermal energy directly into electrical energy. With the development of thermoelectric technology, the demand for thermoelectric materials with high thermoelectric performance, high strength and high plasticity at room temperature is increasing. The performance of thermoelectric materials is characterized by the dimensionless thermoelectric figure of merit (ZT), where ZT = S 2 σT / κ, where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature.

[0003] At present, most traditional thermoelectric materials are brittle, have extremely poor processability, low strength, and poor structural stability during application. Summary of the invention

[0004] The object of the present invention is to provide a high-strength and high-plasticity thermoelectric composite material and a preparation method and application thereof. The thermoelectric composite material provided by the present invention has high strength, high plasticity and high thermoelectric performance.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a thermoelectric composite material, the chemical composition of which is Mg 3.2 Sb 1.5 Bi 0.49 Te 0.01 -xTiB2; wherein x is the molar mass fraction, 0.01≤x≤0.05; the TiB2 in the thermoelectric composite material is nano-TiB2.

[0007] Preferably, the x is 0.03 to 0.05.

[0008] The present invention also provides a method for preparing the thermoelectric composite material described in the above scheme, comprising the following steps:

[0009] (1) ball milling Mg, Bi, Sb, Te and TiB2 in an inert atmosphere to obtain a precursor powder;

[0010] (2) Sintering the precursor powder to obtain the thermoelectric composite material.

[0011] Preferably, the TiB2 is TiB2 powder; the particle size of the TiB2 powder is 50 to 100 nm.

[0012] Preferably, the molar ratio of Mg to TiB2 is 3.2:0.01-0.05; the molar ratio of Bi to TiB2 is 0.49:0.01-0.05; the molar ratio of Sb to TiB2 is 1.5:0.01-0.05; and the molar ratio of Te to TiB2 is 0.01:0.01-0.05.

[0013] Preferably, the ball mill is a vibration ball mill; the rotation speed of the ball mill is 1000-1500 rpm; the running rate of the ball mill fixture is 850-890 cycles / minute; the ball milling time is 3-10 hours; the ball milling method is: stop ball milling for 1 hour every 2 hours.

[0014] Preferably, the sintering pressure is 40-60 MPa; the sintering temperature is 750-850° C.; and the sintering time is 10-20 min.

[0015] Preferably, the sintering temperature raising procedure is: raising the temperature to 600-650° C. within 4-6 minutes, and then raising the temperature to the sintering temperature within 5-6 minutes.

[0016] Preferably, after the sintering, the obtained reaction system is further cooled; the cooling is: reducing the pressure to 0.05-0.1 MPa within 1-2 minutes, and then cooling to room temperature with the furnace.

[0017] The present invention also provides the use of the thermoelectric composite material described in the above scheme or the thermoelectric composite material obtained by the preparation method described in the above scheme in the field of thermoelectric devices.

[0018] The present invention provides a thermoelectric composite material. The present invention introduces nano-TiB2, which can form an energy barrier with a matrix, and improves the Seebeck coefficient without significantly reducing the electrical conductivity; at the same time, the nano-pores generated by the sintering of Mg3(Sb,Bi)2 and the composite nano-TiB2 jointly optimize and adjust the thermal conductivity, and finally the power factor and thermal conductivity of the material are synergistically optimized; the nano-pores and the composite nano-TiB2 synergistically improve the mechanical properties of the material. The thermoelectric composite material provided by the present invention has high plasticity, high compressive strength, high hardness and high thermoelectric performance, excellent mechanical properties, good processability, non-toxic elements, and low cost.

[0019] The results of the embodiments show that the room temperature thermoelectric figure of merit of the thermoelectric composite material provided by the present invention is about 0.64, the average thermoelectric figure of merit at 323-773K is 1.24, the Vickers hardness is 0.71GPa, and the compressive strength is 730MPa while maintaining a 45% compressive strain.

[0020] The present invention also provides a method for preparing the thermoelectric composite material described in the above scheme. The preparation method provided by the present invention has simple steps, convenient operation and high feasibility.

[0021] The present invention also provides the application of the thermoelectric composite material described in the above scheme or the thermoelectric composite material obtained by the preparation method described in the above scheme in the field of thermoelectric devices. The thermoelectric composite material provided by the present invention has high strength, high plasticity and high thermoelectric performance, and has great application potential in thermoelectric devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 The electrical conductivity curves of the thermoelectric composite materials of Examples 1 to 3 and Comparative Example 1;

[0024] Figure 2 is a graph showing the Seebeck coefficient of the thermoelectric composite materials of Examples 1 to 3 and Comparative Example 1;

[0025] Figure 3 The power factor curves of the thermoelectric composite materials of Examples 1 to 3 and Comparative Example 1;

[0026] Figure 4 The thermal conductivity curves of the thermoelectric composite materials of Examples 1 to 3 and Comparative Example 1;

[0027] Figure 5 The thermoelectric figure of merit of the thermoelectric composite materials of Examples 1 to 3 and Comparative Example 1;

[0028] Figure 6 is a Vickers hardness diagram of the thermoelectric composite materials of Examples 1 to 3 and Comparative Example 1;

[0029] Figure 7 It is a compressive stress-strain curve diagram of the thermoelectric composite materials of Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0030] The present invention provides a thermoelectric composite material, the chemical composition of which is Mg 3.2 Sb 1.5 Bi 0.49 Te 0.01 -xTiB2; wherein x is the molar mass fraction, 0.01≤x≤0.05; the TiB2 in the thermoelectric composite material is nano-TiB2.

[0031] In the present invention, the x is preferably 0.03 to 0.05, and specifically can be 0.03, 0.035, 0.04, 0.045 or 0.05. The present invention improves the thermoelectric properties and mechanical properties of the material by adjusting the content of nano-TiB2.

[0032] In the present invention, the calculation formula of x is specifically:

[0033] x = M2 × m / M1;

[0034] Where M1 is Mg 3.2 Sb 1.5 Bi 0.5 Te 0.01 M2 is the total molar mass of TiB2, M2 is the molar mass of TiB2, and m is the mass of TiB2 required.

[0035] The present invention introduces nano-TiB2. The nano-TiB2 heterogeneous powder can form an energy barrier with the matrix, thereby improving the Seebeck coefficient without significantly reducing the electrical conductivity. At the same time, the nano-pores generated by sintering Mg3(Sb, Bi)2 and the composite nano-TiB2 jointly regulate the thermal conductivity of the material, ultimately improving the room temperature ZT of the material. In addition, the nano-pores generated by sintering will weaken stress concentration and improve the plasticity of the material. The composite nano-TiB2 will also block the movement of dislocations and enhance the mechanical properties of the material.

[0036] The present invention also provides a method for preparing the thermoelectric composite material described in the above scheme, comprising the following steps:

[0037] (1) ball milling Mg, Bi, Sb, Te and TiB2 in an inert atmosphere to obtain a precursor powder;

[0038] (2) Sintering the precursor powder to obtain the thermoelectric composite material.

[0039] The present invention ball-mills Mg, Bi, Sb, Te and TiB2 in an inert atmosphere to obtain a precursor powder. The present invention has no particular limitation on the sources of the Mg, Bi, Sb, Te and TiB2, and commercial products well known to those skilled in the art can be used.

[0040] In the present invention, the Mg is preferably Mg particles; the purity of the Mg is preferably 99.95%; the Bi is preferably Bi particles; the purity of the Bi is preferably 99.999%; the Sb is preferably Sb particles; the purity of the Sb is preferably 99.99%; the Te is preferably Te powder; the purity of Te is preferably 99.99%; the TiB2 is preferably TiB2 powder; the particle size of the TiB2 powder is preferably 50 to 100 nm, specifically 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm; the purity of the TiB2 is preferably 99.9%.

[0041] In the present invention, the molar ratio of Mg to TiB2 is preferably 3.2:0.01-0.05, specifically 3.2:0.01, 3.2:0.02, 3.2:0.03, 3.2:0.04 or 3.2:0.05. The present invention adds excessive Mg to prevent magnesium volatilization caused by long-term heat preservation, ensuring that the thermoelectric composite material is an n-type semiconductor.

[0042] In the present invention, the molar ratio of Bi to TiB2 is preferably 0.49:0.01 to 0.05, specifically 0.49:0.01, 0.49:0.02, 0.49:0.03, 0.49:0.04 or 0.49:0.05.

[0043] In the present invention, the molar ratio of Sb to TiB2 is preferably 1.5:0.01 to 0.05, specifically 1.5:0.01, 1.5:0.02, 1.5:0.03, 1.5:0.04 or 1.5:0.05.

[0044] In the present invention, the molar ratio of Te to TiB2 is preferably 0.01:0.01-0.05, specifically 0.01:0.01, 0.01:0.02, 0.01:0.03, 0.01:0.04 or 0.01:0.05. While adding excess Mg, the present invention limits the usage ratio of each element to ensure that each element fully plays its role and improves the thermoelectric performance of the thermoelectric composite material.

[0045] In the present invention, the inert atmosphere is preferably argon; the water and oxygen content of the inert atmosphere is preferably less than 1 ppm, specifically 0.9 ppm, 0.7 ppm, 0.5 ppm, 0.4 ppm, 0.3 ppm, 0.2 ppm or 0.1 ppm. Since the Mg element easily reacts with water and oxygen in the air, resulting in a sharp drop in the power factor of the material, the batching of the present invention embodiment is carried out in a glove box filled with argon.

[0046] In the present invention, the ball mill is preferably a vibration ball mill; the rotation speed of the ball mill is preferably 1000-1500rpm, specifically 1000rpm, 1100rpm, 1200rpm, 1300rpm, 1400rpm or 1500rpm; the fixture running speed of the ball mill is preferably 850-890 cycles / minute, specifically 850 cycles / minute, 860 cycles / minute, 875 cycles / minute or 890 cycles / minute. The present invention adopts the above-mentioned ball milling parameters to ensure the thoroughness of ball milling and the stability of ball milling products, thereby ensuring the repeatability of material preparation.

[0047] In the present invention, the ball milling equipment is preferably a Spex ball mill; the ball milling time is preferably 3 to 10 hours, specifically 3 hours, 5 hours, 7 hours or 10 hours; the ball milling method is preferably: stop ball milling for 1 hour every 2 hours.

[0048] In the present invention, after the ball milling, the inner wall of the ball milling equipment is preferably scraped in an inert atmosphere, and the ball milling is further performed for 1 to 3 minutes. Through the above operation, the present invention prevents uneven ball milling caused by damage to the ball mill and agglomeration of the ball milled powder, ensures the completeness of the ball milling powder reaction and the uniformity of element distribution, and prevents the presence of large particles from affecting sintering.

[0049] In a specific embodiment of the present invention, preferably 6-10 g of raw materials (Mg, Bi, Sb, Te and TiB2) are weighed each time and placed in a ball mill containing two 0.5-inch stainless steel balls. The present invention ensures the thoroughness of the ball milling process by controlling the input amount of the ball milling raw materials.

[0050] After obtaining the precursor powder, the present invention sintered the precursor powder to obtain the thermoelectric composite material. In the present invention, the sintering is preferably spark plasma sintering.

[0051] In the present invention, the sintering pressure is preferably 40-60 MPa, specifically 40 MPa, 45 MPa, 50 MPa, 55 MPa or 60 MPa, more preferably 50 MPa.

[0052] In the present invention, the sintering temperature is preferably 750-850°C, specifically 750°C, 760°C, 770°C, 790°C, 800°C, 810°C, 830°C or 850°C, more preferably 800°C.

[0053] In the present invention, the sintering time is preferably 10 to 20 minutes, specifically 10 minutes, 12 minutes, 14 minutes, 15 minutes, 16 minutes, 18 minutes or 20 minutes. The present invention limits the sintering parameters to achieve a full reaction of the precursor powder, adjust the grain size and pore size, generate a variety of nanopores, and thus improve the thermoelectric performance of the thermoelectric composite material.

[0054] In the present invention, the sintering temperature rise program is preferably: heating to 600-650°C within 4-6 minutes, and then heating to the sintering temperature within 5-6 minutes. The present invention adopts the above sintering temperature rise program to fully sinter the precursor powder. The higher sintering temperature and holding time also make the grain size grow fully, and bring a large number of nanopores, ensuring the electrical conductivity and thermal conductivity of the material.

[0055] In the present invention, after the sintering, the obtained reaction system is preferably cooled down; the cooling down is preferably: reducing the pressure to 0.05-0.1 MPa within 1-2 minutes, and then cooling to room temperature with the furnace.

[0056] The preparation method of the thermoelectric composite material provided by the present invention allows the matrix powder (Mg, Bi, Sb and Te) and the nano-TiB2 powder to be fully sintered by limiting the process parameters of ball milling and sintering, and promotes the full growth of grain size and the formation of nano-pores, thereby further improving the thermoelectric performance of the thermoelectric composite material.

[0057] The present invention also provides the use of the thermoelectric composite material described in the above scheme or the thermoelectric composite material obtained by the preparation method described in the above scheme in the field of thermoelectric devices.

[0058] The thermoelectric composite material provided by the present invention has high strength, high plasticity and high thermoelectric performance, and has great application potential in thermoelectric devices. The results of the embodiment show that the room temperature thermoelectric figure of merit of the thermoelectric composite material provided by the present invention is about 0.64, the average thermoelectric figure of merit at 323-773K is 1.24, the Vickers hardness is 0.71GPa, and the compressive strength is 730MPa when the compressive strain is maintained at 45%.

[0059] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0060] Example 1

[0061] The thermoelectric composite material prepared in this embodiment has a chemical composition of Mg3Sb 1.5 Bi 0.49 Te 0.01 -0.03TiB2.

[0062] The preparation method of the thermoelectric composite material described in this embodiment has the following specific steps:

[0063] (1) 1.6591 g of Mg metal particles, 3.8967 g of Sb metal particles, 2.1844 g of Bi metal particles, 0.02676 g of Te metal powder and 0.2330 g of nano-TiB2 powder were weighed in an argon atmosphere with a water and oxygen content of less than 1 ppm, wherein the molar ratio of Mg metal particles, Sb metal particles, Bi metal particles and Te metal powder was 3.2:1.5:0.49:0.01, and the content of nano-TiB2 was Mg3Sb 1.5 Bi 0.49 Te 0.01 3% of the total molar mass; and the weighed Mg metal particles, Sb metal particles, Bi metal particles, Te metal powder and TiB2 nanopowder were added to a spex ball mill containing two 0.5-inch stainless steel balls and ball-milled for 5 hours. The mill was run for 1 hour, and then the powder on the wall of the ball mill was scraped off in the glove box every 2 hours, and the powder was put into the jar for further ball milling. After the ball milling was completed, the powder was ball-milled for another 1 minute to ensure that the precursor powder obtained had no agglomerated particles; the rotation speed of the ball mill was 1500 rpm, and the fixture operation rate was 875 cycles / minute;

[0064] (2) The precursor powder obtained in step (1) is loaded into a graphite mold in an inert atmosphere, and the graphite mold is placed in a spark plasma sintering furnace. Under a pressure of 50 MPa, the temperature is raised to 610° C. within 5 minutes, and then the temperature is raised to 800° C. within 5 minutes. Spark plasma sintering is performed at 800° C. for 15 minutes. After the sintering is completed, the pressure is reduced to 0.05 MPa within 1 minute, and then the furnace is cooled to room temperature to obtain Mg3Sb 1.5 Bi 0.49 Te 0.01 -0.03TiB2 thermoelectric composite material.

[0065] Example 2

[0066] The preparation method of this embodiment is the same as that of embodiment 1, except that the chemical composition of the thermoelectric composite material is Mg3Sb 1.5 Bi 0.49 Te 0.01 -0.01TiB2; accordingly, the raw materials are 1.6920g of Mg metal particles, 3.9733g of Sb metal particles, 2.2277g of Bi metal particles, 0.0275g of Te metal powder and 0.0792g of nano-TiB2 powder, wherein the content of nano-TiB2 is Mg3Sb 1.5 Bi 0.49 Te 0.011% of the total molar amount; other details are the same as in Example 1.

[0067] Example 3

[0068] The preparation method of this embodiment is the same as that of embodiment 2, except that the chemical composition of the thermoelectric composite material is Mg3Sb 1.5 Bi 0.49 Te 0.01 -0.05TiB2; accordingly, the raw materials are 1.6275g of Mg metal particles, 3.8219g of Sb metal particles, 2.1428g of Bi metal particles, 0.02670g of Te metal powder and 0.3809g of nano-TiB2 powder, wherein the content of nano-TiB2 is Mg3Sb 1.5 Bi 0.49 Te 0.01 5% of the total molar amount, and the rest is the same as in Example 2.

[0069] Comparative Example 1

[0070] The preparation method of this comparative example is the same as that of Example 1, except that: the nano-TiB2 powder is not compounded, and the chemical composition of the thermoelectric material is Mg3Sb 1.5 Bi 0.49 Te 0.01 ; Correspondingly, the raw materials are 1.7089g of Mg metal particles, 4.0130g of Sb metal particles, 2.2500g of Bi metal particles and 0.028g of Te metal powder, wherein the molar ratio of Mg metal particles, Sb metal particles, Bi metal particles and Te metal powder is 3.2:1.5:0.49:0.01; the rest is the same as Example 1.

[0071] Comparative Example 2

[0072] The preparation method of this comparative example is the same as that of Example 1, except that: the nano-TiB2 powder is not compounded, and the chemical composition of the thermoelectric material is Mg3Sb 1.5 Bi 0.49 Te 0.01 ; Correspondingly, the raw materials are 1.7089g of Mg metal particles, 4.0130g of Sb metal particles, 2.2500g of Bi metal particles and 0.028g of Te metal powder, wherein the molar ratio of Mg metal particles, Sb metal particles, Bi metal particles and Te metal powder is 3.2:1.5:0.49:0.01; the sintering temperature is 750°C, and the rest is the same as Example 1.

[0073] Performance Testing

[0074] The electrical performance test of the thermoelectric composite materials obtained in Examples 1 to 3 and Comparative Example 1 was conducted using the LSR-3 electrical performance test system. The test curve of electrical conductivity is shown in FIG. Figure 1 As shown, the test curve of the Seebeck coefficient is as follows Figure 2 As shown, the test curve of power factor is as follows Figure 3 As shown. Figures 1 to 3 It can be seen that after TiB2 is compounded into the matrix, the electrical conductivity decreases slightly, while the Seebeck coefficient increases significantly, which improves the power factor of the prepared thermoelectric composite material.

[0075] The thermal diffusion coefficient F of the thermoelectric composite materials obtained in Examples 1 to 3 and Comparative Example 1 was tested by laser flash method (LFA-457 laser thermal conductivity meter), and the sample density D was measured by Archimedes drainage method. d and formula C p [J -1 K -1 ]=3NR / MW·(1+1.3×10 -4 ×T-4×10 -3 ×T 2 ) Calculated heat capacity C p , and then calculate the total thermal conductivity κ according to the following formula: κ = C p D d The total thermal conductivity is as follows: Figure 4 As shown. Figure 4 It can be seen that when the composite amount of nano-TiB2 is small, the thermal conductivity of the thermoelectric composite material will decrease compared with the matrix, but as the composite amount increases, the thermal conductivity of the material will increase.

[0076] Using the formula ZT=S 2 σT / κ tot The thermoelectric merits of the thermoelectric composite materials obtained in Examples 1 to 3 and Comparative Example 1 were calculated, and the results are as follows: Figure 5 As shown. Figure 5 It can be seen that after compounding nano-TiB2, the thermoelectric performance of the material is improved overall.

[0077] The surfaces of the thermoelectric composite materials obtained in Examples 1 to 3 and Comparative Example 1 were polished, and then the Vickers hardness was measured using a Vickers hardness tester (MH-50 microhardness tester). The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the Vickers hardness of the thermoelectric composite material of the present invention increases with the increase of the composite amount of nano-TiB2.

[0078] The thermoelectric composite materials obtained in Example 1 and Comparative Examples 1-2 were cut into long rods of 4×2×2 mm, and the six surfaces of the long rods were polished smooth. A compression test was performed using a universal testing machine (Instron 5982). The results are as follows: Figure 7 As shown. Figure 7 It can be seen that after compounding nano-TiB2, the compressive strain of the thermoelectric composite material prepared by the present invention decreases slightly, but can still be maintained at more than 40%, and the compressive strength is greatly improved.

[0079] It can be seen from the above embodiments that the thermoelectric composite material provided by the present invention has a thermoelectric figure of merit improved in the entire temperature range due to the simultaneous improvement of power factor and thermal conductivity. At the same time, due to the compounding of nano-TiB2, the Vickers hardness and compressive strength of the thermoelectric composite material are improved while maintaining plasticity, and the comprehensive performance is excellent.

[0080] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A thermoelectric composite material, characterized in that: Chemical composition: Mg 3.2 Sb 1.5 Bi 0.49 Te 0.01 -x TiB2; Wherein, x is the molar mass fraction, 0.01≤x≤0.05; The TiB2 in the thermoelectric composite material is nano-TiB2.

2. The thermoelectric composite material according to claim 1, characterized in that: The x is 0.03 to 0.

05.

3. The method for preparing the thermoelectric composite material according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) ball milling Mg, Bi, Sb, Te and TiB2 in an inert atmosphere to obtain a precursor powder; (2) Sintering the precursor powder to obtain the thermoelectric composite material.

4. The preparation method according to claim 3, characterized in that: The TiB2 is TiB2 powder; The particle size of the TiB2 powder is 50 to 100 nm.

5. The preparation method according to claim 3 or 4, characterized in that: The molar ratio of Mg to TiB2 is 3.2:0.01-0.05; The molar ratio of Bi to TiB2 is 0.49:0.01-0.05; The molar ratio of Sb to TiB2 is 1.5:0.01-0.05; The molar ratio of Te to TiB2 is 0.01:0.01-0.

05.

6. The preparation method according to claim 3, characterized in that: The ball mill is a vibration ball mill; The rotation speed of the ball mill is 1000-1500 rpm; The ball mill fixture running rate is 850-890 cycles / minute; The ball milling time is 3 to 10 hours; The ball milling method is: stop ball milling for 1 hour every 2 hours.

7. The preparation method according to claim 3, characterized in that: The sintering pressure is 40-60 MPa; The sintering temperature is 750-850°C; The sintering time is 10 to 20 minutes.

8. The preparation method according to claim 3 or 7, characterized in that: The sintering temperature raising procedure is: raising the temperature to 600-650° C. within 4-6 minutes, and then raising the temperature to the sintering temperature within 5-6 minutes.

9. The preparation method according to claim 3 or 7, characterized in that: After the sintering, the obtained reaction system is cooled; The temperature reduction is as follows: reducing the pressure to 0.05-0.1 MPa within 1-2 minutes, and then cooling to room temperature along with the furnace.

10. Use of the thermoelectric composite material according to any one of claims 1 to 2 or the thermoelectric composite material obtained by the preparation method according to any one of claims 3 to 9 in the field of thermoelectric devices.

Citation Information

Patent Citations

  • Method for preparing TiB2 strengthening MgAlB14 superhard material

    CN101418397A

  • N-type antimony trimagnesium alloy thermoelectric material with high mobility and preparation method thereof

    CN109616568A

  • Full-temperature-range high-performance n-type Mg-Sb-based thermoelectric material and preparation method thereof

    CN112038473A

  • Thermoelectric conversion material and thermoelectric transducer using the same

    JP2019207983A

  • Reduced oxides having large thermoelectric ZT values

    US20130240801A1